Positive Impact of Balinese Folktale Literacy Learning on Students' Social Attitudes and Reading Ability - Jayadiningrat, Made Gautama; Widiani, Ni Komang (Jurnal Pendidikan dan Pengajaran, 2021)
This paper reports the effect of Balinese folktale literacy learning on elementary students’ reading ability and social attitudes. The type of research is pseudo-experimental research with a non-equivalent post-test-only control group design. The population in this study was 129 students. The sample was selected by using random sampling techniques.  23 students were treated as an experimental group and 27 students were treated as a control group. The data were obtained by administering multiple-choice tests and distributing questionnaires. The data were analyzed by using descriptive statistical analysis techniques and inferential statistics, i.e., Manova-test.  The data of this study were also described through the classification level of each data group by using five conversion guidelines. The results showed that there was a significant difference between the reading ability and the social attitudes of the students taught by using folktale literacy learning and those who were taught by using conventional learning.  It can be seen from the Sig.< value of 0.05. Based on these results, it can be concluded that Balinese folktale literacy learning affected reading ability and social attitudes of  elementary students.